Heavy metals accumulation in lichens Parmeliaceae and mahogany bark as an indicator of air and pollution levels in several locations in Bandung City - Putri Nurul Fitriyyah; Taufikurahman (Indonesian Society for Biochemistry and Molecular Biology, 2023)
Background: Lichens and tree bark are well-known biomonitoring tools for accumulating pollutants in their tissues over an extended period. Objective: This study aims to determine the concentration of heavy metals accumulated in lichens and tree bark across various locations in Bandung City, analyze the impact of heavy metal accumulation on lichen diversity, and assess the lichen cover area on tree bark. Methods: Lichen and bark samples were collected from mahogany trees using plotless sampling at a height of 100 cm, employing a quadrat size of 20x32 cm² above the ground. A total of 25 sampling stations were distributed across five locations in Bandung City, including city parks, an urban forest park, and a bus station. The samples were analyzed using Atomic Absorption Spectrophotometry (AAS) to measure the concentration of heavy metals. Results: The results revealed that lichens and bark from Persib City Park (PCP) contained the highest concentration of chromium (Cr), with 17.08 μg/kg in lichens and 30.03 μg/kg in the bark, as well as lead (Pb), with 24.38 μg/kg in lichens and 15.49 μg/kg in the bark. Conversely, lichens and bark from Djuanda Forest Park (DFP) exhibited the lowest concentration of chromium (3.74 μg/kg in lichens and 3.56 μg/kg in the bark) and lead (3.74 μg/kg in lichens and 2.06 μg/kg in the bark). PCA analysis indicated that the accumulation of heavy metals in lichens and bark was associated with environmental factors, such as traffic density and bark pH. Conclusion: The accumulation of heavy metals in lichens and bark exhibited a negative correlation with lichen diversity and the area of lichen cover on the bark.